Haematological Profile Of Purnathadi Strain Of Nagpuri Buffalo - Kuralkar, Prajakta; Dhenge, S.A.; Kuralkar , S.V. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
The present study was carried out to investigate haematological profile of lactating and nonlactating Purnathadi buffalo in different season. A total 144 blood samples were collected from six lactating and six nonlactating females of Purnathadi buffalo every month for one year. The total leukocyte count (TLC) and lymphocytes (L) were significantly higher in summer, while, Total Erythrocyte Count (TEC), Haemoglobin (Hb), Packed Cell Volume (PCV), Eosinophils (M) and Monocytes (M), values were significantly lower in summer than winter and rainy season.
Keywords: Haematological values; Purnathadi buffaloes; seasonal effect; lactating; nonlactating